Faktor- Faktor yang Mempengaruhi Perilaku Bidan untuk Melakukan Pemeriksaan Papsmear di Kabupaten Bantul - Tri Wahyuni; Nanik Setiyawati; Anita Rahmawati (Jurnal Kesehatan Ibu dan Anak, 2017)
The problem of women's reproductive health is the increased infection of reproductive organs, causing cancer, including cervicalcancer, the second leading cause of death in women. Midwives are health workers and exemplary for the community as well aswomen who are susceptible to cervical cancer. A preliminary study of 10 midwives found 8 people not doing papsmear because ofshame and fear if the results were positive. The aim of this research is to know the factors that influence the behavior of the midwife toperform papsmear examination. This research is an analytic survey research with cross sectional approach. The number of samplesof 79 health center midwives Bantul regency recorded in the Health Profile of Bantul Regency on 2016. Data collection techniquesusing questionnaires. Data analysis using SPSS 16.0 Program with descriptive frequencies test on univariate analysis and chisquare test on Bivariate analysis. The result of univariate test showed that midwife attitude was dominated by negative responses(50.6%), low category to belief toward midwife support (63.3%), midwives belief to leadership support (57.0%), midwives belief topeer support (50.6%) in support of midwife Do a papsmear check. Behavior of midwife performing papsmear is dominated byirregular pattern (58.2%). The result of bivariate test showed that there was a correlation between midwife's attitude (0.030),midwife's belief in husband support (0.025), midwives belief on leadership support (0.001), and midwives belief in peer support(0.000) on midwife behavior to perform papsmear.